Nanocrystalline K-F zeolite from rice husk silica as an eco-friendly solid base catalyst for the synthesis of jasminaldehyde under microwave irradiation - Wong, Siew-Fang; Krittanun Deekomwong,; Jatuporn Wittayakun,; Ling, Tau Chuan; Oki Muraza,; Farook Adam,; Ng, Eng-Poh (Penerbit Universiti Kebangsaan Malaysia, 2018)
Nanocrystalline aluminosilicate F-type zeolite (K-F, EDI-type structure) was synthesized in an organic template-free system using rice husk ash (RHA) silica source and microwave energy. The morphology, crystallite size, chemical composition, crystallographic and basicity properties of the nanocrystals were studied by using various characterization techniques. The results showed that fully crystalline K-F zeolite (Si/Al ratio = 1.26) with flattened cuboid-like shaped could be obtained within 2 min of crystallization which was considerably very fast. In addition, K-F zeolite nanocrystals was also tested as a solid base catalyst in the microwave-enhanced Aldol condensation reaction of heptanal with benzaldehyde and the six catalytic parameters were studied and optimized. The nanosized K-F zeolite crystals showed good catalytic performance in the studied reaction with 77.1% heptanal conversion and 69.5% jasminaldehyde selectivity under optimum reaction condition. The nanocatalyst was reusable and no significant loss in its catalytic reactivity was observed even after five consecutive reaction cycles.